The effect of anisotropic bending elasticity on the structure of bent DNA - Mohammad-Rafiee, F; Golestanian, R (2005)
The response of a short DNA segment to bending is studied, taking into account the anisotropy in the bending rigidities. It is shown that due to the helical structure of DNA, the anisotropy in the bending rigidities can lead to the formation of kinks and modulations in the curvature, depending on the values of the elastic constants. The typical wavelength for the modulations, or the distance between the neighbouring kinks, is found to be set by half of the DNA pitch. © 2005 IOP Publishing Ltd.